THE GENERAL DATA PROTECTION LAW IN LABOR RELATIONS - : AN ANALYSIS OF THE EFFECTS RESULTING FROM THE CIRCULATION OF PERSONAL DATA IN THE WORKPLACE - Rufino da Cunha , Lucas; Barbosa Soares , Jaqueline; Ingrid Cardoso Martins, Alexia (Revista Gênero e Interdisciplinaridade, 2021)
This work has the difficult task of explaining the intimate relationship that the new General Law for the Protection of Personal Data has on labor relations in the labor environment, since the question of its nature is actively manifested in the phases that precede and finalize a contract of employment work, and, therefore, the demonstration of how an effective treatment of personal data will bring immeasurable benefits to all agents that include such a relationship, while also not discarding the opposite effect whose can be potentially harmful, being essentialfor a contemporary legal study.